Healthier and tastier - Azlan, Azrina; Chan, Shuk Huei (Universiti Putra Malaysia Press, 2020)
The selection of ingredients and preparation of food that involves modification of the recipe is essential towards a healthier option. Recipes can be modified to include more fibre, less fat, especially the saturated fat, less added sugars, low salt and lower energy content. Recipe modification also enhancing the nutritional value of cooked food by increasing proteins, providing essential amino acids and essential fatty acids for growing up children, elderly and unhealthy individual. The modifications proposed in this book are intended to benefit many individuals and students for better overall health through healthier and tastier food. In this book, the original recipe is kept with a clear suggestion of modification followed by improvement of important nutritional value.